Chuanxiong improves angiogenesis via the PI3K/AKT/Ras/MAPK pathway based on network pharmacology and DESI-MSI metabolomics - Cheng, Xue-hao; Yang, Xue-xin; Cui, He-rong; Zhang, Bei-bei; Chen, Ke-dian; Yang, Xiao-yun; Jiao, Jing-yi; Du, Ya-wen; Zhang, Qi; Zheng, Jia-xin; Xie, Wei; Li, Fei-fei; et al. (Frontiers in Pharmacology, 2023)
Chuanxiong, a traditional Chinese medicine, has been proved to treat a variety of cardiovascular and cerebrovascular diseases by promoting angiogenesis.However,the mechanism underlying of Chuanxiong's pro-angiogenesis impact is currently unknown.This study aimed to determine whether Chuanxiong can promote angiogenesis in vivo and vitro, and to explore the underlying mechanism.First,the network pharmacology analysis was used to predict prospective targets , build a protein-protein network and enrich the pathways.Then the chorioallantoic membrane test on quails were used to assess the proangiogenic effects of Chuanxiong in vivo. Western blot analysis, real-time PCR the scratch test, and the tube formation assay were performed to assess the effects of Chuanxiong in vitro.The major metabolic pathways associated with Chuanxiong were subsequently analyzed by non-targeted metabolomics.As a result of network pharmacological analysis, 51 collective targets of Chuanxiong and angiogenesis were identified, which are mainly associated with PI3K/AKT/Ras/MAPK pathway.The biological verification results showed that Chuanxiong treatment could increase the vessel numbers and vessel area in qCAM models. Meanwhile,Chuanxiong contribute to HUVEC proliferation, tube formation, migration, by encouraging scratch healing rates and boosting tube branch points.In addition, the levels of VEGFR2,MAPK and PI3K were elevated compared to the control group.The western blot analysis also confirmed Chuanxiong could promote an increase in AKT,FOXO1 and Ras. Furtheremore,Metabolomic results showed that the proangiogenic effect of Chuanxiong is associated with glycine, serine and threonine metabolism. In conclusion,this study clarified that Chuanxiong could promote angiogenesis in vivo and vitro,which are connected to the regulation of PI3K/AKT/Ras/MAPK pathway.